Pengaruh Pijat Oksitosin Terhadap Kecukupan ASI Pada Ibu Nifas Di PMB NH Sawangan Kota Depok Jawa Barat - Azis, Aninditya; Herawati, Nani (Akademi Kebidanan Bunga Husada Samarinda, 2023)
baby does not get adequate breast milk, one of the efforts to increase the adequacy of breast milk is oxytocin massage. This study aims to determine the effect of oxytocin massage on the adequacy of breast milk in postpartum mothers at PMB NH Sawangan, Depok City. This type of research is pre-experimental with a one group pretest-posttest design. The population of this study were all postpartum mothers at PMB NH Sawangan, Depok City. The research sample was 30 postpartum mothers, taken by purposive sampling. The results showed The paired sampel t-test bivariate statistical test shows a value (p value 0.001). There is an effect of oxytocin massage on the adequacy of breast milk in postpartum mothers at PMB NH Sawangan, Depok City